The Antibiotic Resistance Genes blaSHV, blaOXA-48, blaTEM and blaIMP in Pseudomonas aeruginosa Isolated from Respiratory Tract Infections in Baghdad, Iraq - Hasan A. Aal Owaif; Mays K. Aldulaimy; Sura A. Abdulateef (International Journal of Biomedicine, 2023)
Background: Pseudomonas aeruginosa (P. aeruginosa) is the most common pathogen associated with respiratory tract infections. Our study aimed to detect the antibiotic resistance profile and some antibiotic resistance genes of local isolates of P. aeruginosa from respiratory tract infections and to determine the biofilm formation by these isolates. Methods and Results: Two hundred sputum samples were obtained from patients with CF from different hospitals in Baghdad from November 2022 to February 2023. Biochemical tests and the VITEK-2 system were used to identify P. aeruginosa isolates. The disc diffusion technique was used in the antibiotic susceptibility test, and the results were identified according to CLSI guidelines 2020. Biofilm formation was performed by the microtiter-plate method and determined using an ELISA reader at OD570. The PCR was performed to detect the blaSHV gene, blaTEM gene, blaIMP gene, and blaOXA-48 gene. Sixty (30%) isolates of P. aeruginosa were identified from 200 sputum samples.The results showed that 93.4% of the isolates were resistant to Amoxicillin-Clavulanic acid, 90% to Nitrofurantoin and Cefepime, 88.4% to Cefotaxime, 85% to Doxycycline, 83.4% to Tobramycin, 81.7% to Tetracycline and 80% to Meropenem. In comparison, 91.6% were sensitive to Ofloxacin, 68.3% to Azithromycin, and 36.6% to Chloramphenicol. All P. aeruginosa isolates were identified as MDR. The results revealed that 55% of the isolates produced strong biofilms, 38.3% produced moderate biofilms, and 6.7% produced weak biofilms. The rates of blaSHV, blaTEM, blaIMP, and blaOXA-48 genes were 28.3%, 60%, 26.6%, and 68.3%, respectively. Conclusion: This study revealed that all isolates showed MDR phenotype. Biofilm formation by P. aeruginosa isolates and the variation in the incidence of antibiotic resistance encoding genes, in addition to the abuse and overuse of antibiotics, are significant reasons for the progress and spread of antibiotic resistance.